Diffuse Pulmonary Lesions Due to Invasive Fungal Infection in an Immune-capable Male: A Case Report - Radhakrishnan, N.; Narayanan, Mathiyazhagan (Dubai Medical Journal, 2025)
Introduction: Invasive fungal pulmonary infection is a fungal illness caused by many species of fungi, including Aspergillus, generally presenting as life-threatening hazards to people with compromised immune systems. Although instances in immunecompetent individuals are infrequent, a recently published report detailed active lung infection within an immune-competent patient at postmortem. We report a rare instance of invasive fungal infection (IFI) in an immune-capable male, exhibiting diffuse systemic lesions. Case Report: A 33-year-old male approached our facility, complaining of chest discomfort and dyspnea lasting for 3 months. Upon clinical examination, he looked emaciated and presented with sinus symptoms. A radiographic examination showed indistinct lesions in the lower left lobe of the lung. Bronchoscopy as well as bronchoalveolar lavage (BAL) were conducted, before the commencement of oral antibiotic treatment. The lavage findings were negative for staining techniques (e.g., acid-fast bacilli (AFB)), and culture demonstrated many septate hyphae on the fungal screen. Histopathological analysis of lung tissue (via bronchoscopy) revealed persistent granulomatous inflammation with apical fungal hyphae, diagnostic of aspergillosis. Further cultures confirmed the presence of Aspergillus fumigatus, leading us to commence voriconazole treatment. The patient had a notable recovery, evidenced by gaining weight and a recovered appetite within a brief timeframe. His symptoms improved within three months of medication, allowing him to return to almost normal life. Conclusion: This case underscores the identification of IFI in an immune-capable patient exhibiting extensive nodular lesions throughout the respiratory tract, mediastinum, and belly. Clinicians must uphold a heightened concern for aspergillosis in persistent pneumonia and diffuse nodular lesions, despite patients having no conventional risk factors.